APOE4 confers transcriptomic and functional alterations to primary mouse microglia - Machlovi, Saima I.; Neuner, Sarah M.; Hemmer, Brittany M.; Khan, Riana; Liu, Yiyuan; Huang, Min; Zhu, Jeffrey D.; Castellano, Joseph M.; Cai, Dongming; Marcora, Edoardo; Goate, Alison M. (Neurobiology of disease, 2022)
Common genetic variants in more than forty loci modulate risk for Alzheimer’s disease (AD). AD risk alleles are enriched within enhancers active in myeloid cells, suggesting that microglia, the brain-resident macrophages, may play a key role in the etiology of AD. A major genetic risk factor for AD is Apolipoprotein E (APOE) genotype, with the ε4/ε4 (E4) genotype increasing risk for AD by approximately 15 fold compared to the most common ε3/ε3 (E3) genotype. However, the impact of APOE genotype on microglial function has not been thoroughly investigated. To address this, we cultured primary microglia from mice in which both alleles of the mouse Apoe gene have been humanized to encode either human APOE ε3 or APOE ε4. Relative to E3 microglia, E4 microglia exhibit altered morphology, increased endolysosomal mass, increased cytokine/chemokine production, and increased lipid and lipid droplet accumulation at baseline. These changes were accompanied by decreased translation and increased phosphorylation of eIF2ɑ and eIF2ɑ-kinases that participate in the integrated stress response, suggesting that E4 genotype leads to elevated levels of cellular stress in microglia relative to E3 genotype. Using live-cell imaging and flow cytometry, we also show that E4 microglia exhibited increased phagocytic uptake of myelin and other substrates compared to E3 microglia. While transcriptomic profiling of myelin-challenged microglia revealed a largely overlapping response profile across genotypes, differential enrichment of genes in interferon signaling, extracellular matrix and translation-related pathways was identified in E4 versus E3 microglia both at baseline and following myelin challenge. Together, our results suggest E4 genotype confers several important functional alterations to microglia even prior to myelin challenge, providing insight into the molecular and cellular mechanisms by which APOE4 may increase risk for AD. [Display omitted] •APOE4 vs APOE3 (E4/E3) mouse microglia in vitro (MG) show reactive morphology and cytokine profile.•E4/E3 MG show increased phagocytic uptake and impaired degradation of myelin.•E4/E3 MG show increased neutral lipid and endolysosomal content.•E4/E3 MG show increased interferon and eIF2 signaling, and repressed translation.•Modulation of eIF2 signaling and cell stress in MG may be a therapeutic lead for AD.